The characteristics of the major apartment areas of Johannesburg and their planning implications - Kahn, Michael (My University, 2015)
This Study is concerned with the socio-demographic, locational and certain planning aspects of multi-storeyed apartment developments in the city of Johannesburg. These developments form part of the great urban-industrial complex of the Witwatersrand and occurs at specific locations within the city, in numerous forms, and in several concentrations of differing geographical extent. The structure of this spatial differentiation of apartments within the morphology of the city reflects the interrelationships of differing demographic characteristics of apartment dwellers, the nature of development, and the setting of the concentrations of apartments. This has implications for planning because of the interaction between population groups and their need for a specific set and mix of social facilities and amenities. These planning implications are of particular relevance to local authorities that not only demarcates the location and type of apartment development , but must also provide or make allowance for the necessary social facilities.
Keywords: Socio-demographic planning; Apartment development; Urban-industrial complexes; Johannesburg